2009
DOI: 10.1002/ajpa.21064
|View full text |Cite
|
Sign up to set email alerts
|

Intensity, repetitiveness, and directionality of habitual adolescent mobility patterns influence the tibial diaphysis morphology of athletes

Abstract: Mobility patterns affect the loads placed on the lower limbs during locomotion and may influence variation in lower limb diaphyseal robusticity and shape. This relationship commonly forms the basis for inferring mobility patterns from hominin fossil and skeletal remains. This study assesses the correspondence between athletic histories, varying by loading intensity, repetition and directionality, measured using a recall questionnaire, and peripheral quantitative computed tomography-derived measurements of tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
195
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 78 publications
4
195
2
1
Order By: Relevance
“…Changes in bone shape of this kind strongly imply localized modeling/remodeling resulting from specific mechanical stimuli (20). Despite some partially contrary evidence in cursorial animals (43), which may be under special constraints (20), a number of both experimental and observational studies of humans support the association between preferential strengthening of the lower limb bones in the A-P plane and greater mobility (30,(34)(35)(36)(37)(38). Thus, our results imply a major reduction in mobility in both sexes beginning in the Neolithic.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Changes in bone shape of this kind strongly imply localized modeling/remodeling resulting from specific mechanical stimuli (20). Despite some partially contrary evidence in cursorial animals (43), which may be under special constraints (20), a number of both experimental and observational studies of humans support the association between preferential strengthening of the lower limb bones in the A-P plane and greater mobility (30,(34)(35)(36)(37)(38). Thus, our results imply a major reduction in mobility in both sexes beginning in the Neolithic.…”
Section: Discussioncontrasting
confidence: 45%
“…It is known that long bone diaphyseal cortices react to imposed mechanical loadings throughout life, changing their cross-sectional geometry to adapt to altered strain magnitudes and distributions, which in turn are dependent on behavioral use of the limbs (20-22, 30, 31). For example, vigorous exercise in humans greatly increases bending strains in the tibia (32,33) and is associated with preferential strengthening in the direction of movement, i.e., running and jumping lead to increases in A-P/M-L strength (30,34,35). Increased A-P/M-L bending strength of the lower limb bones also characterizes more terrestrially mobile populations or subpopulations (36)(37)(38).…”
Section: Significancementioning
confidence: 99%
“…Only those populations living in extremely cold climatic conditions appear to have been affected by non-neutral directional climatic adaptation [27,29,32]. However, in the case of the postcranial skeleton, most studies have suggested relatively potent (non-neutral) effects of climatic adaptation [33][34][35][36][37][38], plasticity related to habitual activity [37,39,40] and the effects of nutritional or environmental stress on growth [41][42][43]. However, there is evidence to suggest that the morphology of some regions of the postcranium (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several evidences support the idea that bone undergoes mechanical adaptation: a) studies with athletes that show an increased bone strength; b) experimental studies with animals that are submitted to vigorous exercise regimens or movement constraints; c) studies of limb disuse (e.g. pathology, zero gravity, immobility) (Haapasalo et al, 2000;Robling et al, 2000;Shaw & Stock, 2009a, 2009b. Thereby an increased strain will stimulate deposition of new bone tissue which strengthen the bone and consequently reduces strain, while decreased strain (e.g.…”
Section: Introductionmentioning
confidence: 99%